Perlindungan Hukum Konsumen dalam Jual Beli yang tidak Sesuai Dengan Perjanjian pada Transaksi E-Commerce - Sholihan Sholihan; Rusydi Rusydi; Shalahudddin Serba Bagus; Amatus Sudin; Annafidzatul Qulub (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
Advances in information and communication technology (internet) are not only to find various information, but some people make it a medium for conducting transactions in e-commerce. The positive aspects of e-commerce transactions, in addition to saving time, are also more certain prices, but that does not mean without weaknesses; for example, the goods purchased are not as promised. Of course, this harms consumers, so there are disputes between consumers and business actors. Therefore, there needs to be legal protection, considering that consumers are often positioned as weak parties. This study examines whether the elements in e-commerce transactions meet the aspects of buying and selling in the Civil Code and how the Consumer Protection Law provides legal protection if the goods purchased by consumers are not by the agreement. This research is a normative legal research using a statutory, concept, and comparative approach. Legal materials are collected through literature research. Legal materials are analysed by quoting and reviewing relevant articles of laws and regulations. At the same time, the opinions of scholars are cited and used as a theoretical basis to answer research questions.The results of the discussion of research problems can conclude that the main elements in e-commerce transactions are buyers, sellers, goods and prices by the aspects of buying and selling in the Civil Code. Still, in e-commerce transactions, additional parties are involved, namely intermediaries. For consumers who feel aggrieved because the goods purchased are not by the agreement, the form of legal protection is to be able to claim compensation through litigation or non-litigation channels.